FAKTOR PENGENDARA SEPEDA MOTOR TIDAK MENGGUNAKAN HELM (Studi Kasus: Jalan Purus IV-V Kelurahan Purus Kecamatan Padan Barat) - Saputra, Rio - (Pendidikan Sosiologi, 2014)
Transportation serves to overcome the communication gap and the distance between the origin and the destination, it was developed for the infrastructure system. In addition to supporting the smooth transportation system also ruquired traffic system that is safe to drive. In order to create a safe and orderly society in road traffic, where the government has made a legislation that is in the form of Act 22 of 2009 on the traffic and road transport, with this rule, the government in this stakeholders such as the police are empowered to crack down on traffic violators, including issues regarding the factors bikers do not use helmets. Regulations regarding the use of helmets has been set up in Act 22 of 2009 Article 57 paragraph (2) of the traffic and road transport that explains mandatory for motorcyclists to wear safety helmets. The purpose of this study was to describe factors motorcyclist not wearing a helmet at ro Padang District West Purus. The theory used in this study is the theory of social action in which social action to obtain a valid understanding of subjective meanings in other words in the form of self introspection. Research using qualitative methods and the type used in this research is to develop a descriptive problem under study, taking informants to do with using a deliberate mechanism (propposive). In collecting data using primary data obtained through observation and in-depth interviews. The unit of analysis of data comprising the steps of data reduction, data presentation and conclusion.From the conclusion, there are many motorcycle riders do not obey traffic discipline that is not using a helmet with various factors: A. Internal factors are: (1). Lack of awareness about public awareness law that not using helmets are very at least, whereas the existing traffic regulation order. (2). Factor is a sense of comfort. That informant stated that the use of helmets they feel less comfortable when using the helmet. (3). Destructive force which resulted in the appearance of his appearance will be damaged if use helmet. (4). Safety is the most important thing any society when riding a motorcycle. B. External factors are: (1). Distance or location of the residence where the destination is close informants and the absence of police at the site (2). Violations of the police is to sanction those who violate the traffic rules.